487 BRAIN DRAIN: THE NEXT GENERATION? PERCEPTIONS OF UGANDAN MEDICAL STUDENTS. Issue 1 (1st January 2007) - Ropers, S.; Nguyen, L.
Abstract : Background: Emigration of African doctors to Western countries has left African countries with inadequate coverage and the unsatisfying situation of educating doctors but losing them soon after their graduation. Gaining a better understanding of the perceptions that medical students have toward emigration will help address its causes and possibly limit the loss of health care personnel. We hypothesized that medical students at Makerere University develop a more favorable attitude toward emigration in the course of their medical training. Study Design and Methods: We conducted the research at Makerere University in Kampala, Uganda. Anonymous questionnaires were distributed to medical students across the 5 years of classes and collected from 258 students. Time commitment was about 15 minutes per questionnaire. Results: The hypothesis could not be proven as stated. Medical students in upper years (3, 4, and 5) were not more likely to indicate a desire to work in another country than students in lower years (1 and 2). However, it was found that upper years were significantly more likely than lower years to be willing to move abroad if the financial offer was better (79.2% vs 67%, p = .031). Upper-year men were significantly more likely to express interest in moving abroad for a better financial offer than lower-year men (83.2% vs 63.5%, p = .007). Whereas 68.3% of upper years thought it was likely or very likely that they would experience occupational risk working in Uganda, only 52.6% of lower years thought so ( p = .014). There was a strong correlation between interest in working in the private sector and willingness to leave the country for a better financial offer ( p = .004). Students interested in working in a rural setting after their training were less likely to say that they would move to another country for a higher-paying job than students interested in urban settings. Conclusion: Results suggest that to prevent further physician efflux in years to come, it will be necessary to improve the pay for doctors, to improve safety conditions in hospitals, and to start modifying the admissions process in medical school by adding personal interviews. This would allow admitting more students interested in working in rural areas and admitting fewer students interested in careers in the private sector.